2015
DOI: 10.1038/nchembio.1848
|View full text |Cite
|
Sign up to set email alerts
|

5-Formylcytosine can be a stable DNA modification in mammals

Abstract: 5-Formylcytosine (5fC) is a rare base found in mammalian DNA and thought to be involved in active DNA demethylation. Here, we show that developmental dynamics of 5fC levels in mouse DNA differ from those of 5-hydroxymethylcytosine (5hmC), and using stable isotope labeling in vivo, we show that 5fC can be a stable DNA modification. These results suggest that 5fC has functional roles in DNA that go beyond being a demethylation intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
210
1
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(225 citation statements)
references
References 25 publications
5
210
1
9
Order By: Relevance
“…The level of 5hmC is known to be a stable mark at high levels in the adult mouse brain (Kinney et al, 2011;Bachman et al, 2014), but relatively very low in embryonic fibroblasts (Kinney et al, 2011). 5fC has been defined as a rare modification found in many tissues (Booth et al, 2014;Bachman et al, 2015), but we have observed that the level of 5fC is higher than that of 5hmC in fibroblasts. Although 5fC is rare, it can exist in specific sites with levels comparable to 5meC and 5hmC (Booth et al, 2014).…”
Section: Discussioncontrasting
confidence: 37%
“…The level of 5hmC is known to be a stable mark at high levels in the adult mouse brain (Kinney et al, 2011;Bachman et al, 2014), but relatively very low in embryonic fibroblasts (Kinney et al, 2011). 5fC has been defined as a rare modification found in many tissues (Booth et al, 2014;Bachman et al, 2015), but we have observed that the level of 5fC is higher than that of 5hmC in fibroblasts. Although 5fC is rare, it can exist in specific sites with levels comparable to 5meC and 5hmC (Booth et al, 2014).…”
Section: Discussioncontrasting
confidence: 37%
“…1A) [12,13]. 5hmC, 5fC and 5caC are chemically distinct cytosine modifications that base-pair normally with G and are found at different levels in mammalian genomes [12][13][14][15]. While their individual biological significance is not yet fully understood, the newly discovered 5mC derivatives extend the long-thought binary state of static cytosine modifications to five distinct and possibly dynamic states with yet to be defined epigenetic roles.…”
mentioning
confidence: 94%
“…There is, however, an ongoing debate as to whether the TET-oxidized 5mC derivatives represent DNA demethylation intermediates or have an epigenetic function on their own. In support of an epigenetic function are findings that 5mC derivatives appear to be rather stable in ESCs and tissues (200-6000, 0.2-15 and < 3 ppm total Cs for 5hmC, 5fC and 5caC, respectively) [15,88] and that potential readers can be identified for all of them [92, 93]. Nevertheless, other lines of investigation indicate that the excision of 5fC and 5caC by TDG has functional relevance in ESCs [91].…”
mentioning
confidence: 94%
“…DNA methylation is one of the core epigenetic marks essential for regulating gene expression in normal cell development and differentiation [16]. While 5mC is the most well-characterized, other cytosine modifications have now been discovered, such as 5-hydroxymethycytosine (5hmC), 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC) [17,18]. The functions of these exotic marks are still being elucidated, but 5hmC may play an important role in the central nervous system, where it is prevalent, and in the regulation of pluripotency in stem cells [19,20].…”
Section: Epigenetics Overviewmentioning
confidence: 99%